2020
DOI: 10.1038/s41419-020-2578-x
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 activates Wnt signaling pathway to inhibit granulosa cell apoptosis

Abstract: The TGF-β and Wnt signaling pathways are interrelated in many cell types and tissues, and control cell functions in coordination. Here, we report that SMAD4, a downstream effector of the TGF-β signaling pathway, induces FZD4, a receptor of the Wnt signaling pathway, establishing a novel route of communication between these two pathways in granulosa cells (GCs). We found that SMAD4 is a strong inducer of FZD4, not only initiating FZD4 transcription but also activating FZD4-dependent Wnt signaling and GC apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 69 publications
(88 reference statements)
4
30
0
Order By: Relevance
“…In this study, we attempted to investigate the biological functions of SMAD4 in mammalian ovarian GCs by screening for its target genes and interacting coregulators. Bioinformatics analyses indicate that SMAD4 is crucial for the normal states and functions of GCs, as well as oocyte development and maturation, which is consistent with previous studies [ 23 , 24 ]. Additionally, the differentially expressed genes were identified, and we noticed that the expressions of multiple members in the TGF-β family signaling pathways were influenced in GCs after knockdown of SMAD4, especially the three important receptors (ACVR1B, BMPR2, and TGFBR2) described in this study, which highlighted the feedback regulation activities of SMAD4 in mammal GCs.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we attempted to investigate the biological functions of SMAD4 in mammalian ovarian GCs by screening for its target genes and interacting coregulators. Bioinformatics analyses indicate that SMAD4 is crucial for the normal states and functions of GCs, as well as oocyte development and maturation, which is consistent with previous studies [ 23 , 24 ]. Additionally, the differentially expressed genes were identified, and we noticed that the expressions of multiple members in the TGF-β family signaling pathways were influenced in GCs after knockdown of SMAD4, especially the three important receptors (ACVR1B, BMPR2, and TGFBR2) described in this study, which highlighted the feedback regulation activities of SMAD4 in mammal GCs.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we have attempted to investigate the biological functions of SMAD4 in mammalian ovarian GCs by screening for its target genes and interacting proteins. Bioinformatics analyses indicate that SMAD4 is crucial for the normal states and functions of GCs, as well as oocyte development and maturation, which is consistent with the previous researches [22,28]. Besides, the differentially expressed genes were identi ed and interestingly found multiple members of TGF-β family signaling pathways including three important receptors (ACVR1B, BMPR2, and TGFBR2), which highlights the feedback regulation functions of SMAD4.…”
Section: Discussionsupporting
confidence: 87%
“…Fresh porcine bilateral ovaries were collected and placed in a thermos ask with 37°C PBS and transported back to the laboratory within 1 h. The collected ovaries were washed with PBS 5 times and porcine GCs were harvested from 2-5 mm non-atretic ovarian follicles by using syringe with 22-gauge needle and cultured as previously described [22]. Brie y, the isolated porcine GCs were washed with 37°C PBS containing 1% penicillin and streptomycin three times, and then seeded in cell culture plates with DEME/F12 containing 10% fetal bovine serum (FBS) in a 37°C humid atmosphere with 5% CO 2 .…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…We identified several miRNAs differentially expressed between the patient groups which have not been previously associated with PCOS but are involved in the regulation of gene expression in follicles or in other ovary-related disorders. For example, hsa-miR-224-5p [60], which was up-regulated in the MGC of PCOS women in our study, downregulates SMAD4, which is involved in the regulation of apoptosis of granulosa cells [61]. It has been shown that hsa-miR-203a-3p, hsa-miR-195-5p, hsa-miR-486-3p, and hsa-miR-484 levels are altered in the granulosa cells of women with diminished ovarian reserve [24].…”
Section: Discussionsupporting
confidence: 45%